My hero academia. Vol. 1, Izuku Midoriya: origin - Horikoshi, Kōhei, 1986-; Cook, Caleb D. (San Francisco, California : VIZ Media, 2017)
"What would the world be like if 80 percent of the population manifested superpowers called "Quirks"? Heroes and villains would be battling it out everywhere! Being a hero would mean learning to use your power, but where would you go to study? The Hero Academy of course! But what would you do if you were one of the 20 percent who were born Quirkless? Middle school student Izuku Midoriya wants to be a hero more than anything, but he hasn't got an ounce of power in him. With no chance of ever getting into the prestigious U.A. High School for budding heroes, his life is looking more and more like a dead end. Then an encounter with All Might, the greatest hero of them all, gives him a chance to change his destiny..." -- Back of book.
Izuku Midoriya: origin -- Roaring muscles -- Entrance exam -- Starting line -- Smashing into academia -- What I can do for now -- Costume change?
"First published in Japan in 2014 by Shueisha Inc., Tokyo." -- Colophon.
Reads from back to front and from right to left in the traditional Japanese format.
Rated T for teens.
Translated from the Japanese.
Keywords: High school students -- Comic books, strips, etc. -- Juvenile fiction; Superheroes -- Comic books, strips, etc. -- Juvenile fiction; High schools -- Comic books, strips, etc. -- Juvenile fiction; Schools -- Comic books, strips, etc. -- Juvenile fiction; High school students -- Fiction; Superheroes -- Fiction; High schools -- Fiction; Schools -- Fiction; YOUNG ADULT FICTION / Comics & Graphic Novels / Manga; YOUNG ADULT FICTION / Comics & Graphic Novels/ Superheroes; YOUNG ADULT FICTION / Action & Adventure / General; High school students; High schools; Schools; Superheroes; Superhero comic books, strips, etc; Manga; Graphic novels; Science fiction comics; Graphic novels; Science fiction comics; Graphic novels; Comics (Graphic works)